Influenza virus-specific cytotoxic T cells in man; induction and properties of the cytotoxic cell. - Mcmichael, A; Askonas, B (1978)
Human peripheral blood lymphocytes have been sensitized in vitro to influenza virus antigen. After an induction period of 4--14 days, cytotoxic cells which lyse autologous influenza virus-infected lymphoid cells could be demonstrated. The cytotoxic cell is a T lymphocyte which shows specificity for sensitizing influenza virus type A or B. It cannot distinguish between major subtypes of influenza A virus. The use of virus-infected normal lymphoid cells as target cells overcame the difficulties of nonspecific killing encountered with some transformed cells.